'An Authority from which there can be no appeal': The place of Cicero in Hume's science of man. Issue 3 (September 2020) - Stuart-Buttle, Tim
Abstract : Hume's admiration for the Roman philosopher and statesman, Cicero, is well-known. Yet scholars have largely overlooked how Hume's interpretation of Cicero – initially as a Stoic, and subsequently as an academic sceptic – evolved with Hume's own intellectual development. Moreover, scholars tend to focus on Hume's debts to Cicero with regard either to his epistemological scepticism or his philosophy of religion. This essay suggests instead that Hume's engagement with Cicero was at its most intense, and productive, when evaluating the relationship between morality and religious belief. Closer attention to the place of Cicero in Hume's writings illuminates our understanding of Hume's intellectual development, particularly in the crucial pre- Treatise years. It also, however, shines light on Hume's interpretation of the history of occidental philosophy (not least the consequences of its engagements with Christian theology), and on how Hume saw his own work to relate to this history.